Evoking transformation : visual redress at Stellenbosch University - Fataar, Aslam (African Sun Media, 2021)
"This book is especially timely and will be very influential in the acknowledgment of the importance of institutional transformation in the context of heritage in postcolonial universities in South Africa, Africa, and globally."--Publisher's description